Developing Renewable and Alternative Energy Sources to Improve the Efficiency of Housing Construction and Management - Nezhnikova, Ekaterina; Papelniuk, Oksana; Dudin, Mihail (International Journal of Energy Economics and Policy, 2019)
Demographic, economic and cultural changes increase energy consumption in the housing sector and cause even higher levels of the related greenhouse gas emissions. The goal of this work is to identify opportunities for developing renewable energy sources (RES) in the housing sector to improve its energy efficiency. The results of the study show that the construction industry, and especially the housing sector, can save more energy as compared to other types of the energy use. RES are important in reducing CO2 emissions in the housing sector and in improving the energy efficiency of buildings. In recent years, the production and consumption of energy from renewable sources in the housing sector have increased. However, the main volume of energy consumption in buildings is provided by fossil fuels. The main barriers to the introduction of renewable energy in the DNC housing system are financial ones, as well as logistical problems of biomass transportation and storage. To reduce these barriers, the authors offer a number of measures, including the governmental support for the use of renewable energy in the systems of heat supply and cooling of buildings, as well as the creation of storage facilities for renewable energy. The system of encouraging the use of RES applied in Denmark, which is the world leader according to the use of renewable energy in the housing construction, is considered as an example. Keywords: energy, energy consumption, housing sector, buildings sector, renewable energy sources, DNC. JEL Classifications: Q42, O18 DOI: https://doi.org/10.32479/ijeep.7732